Representation of phonological information in the brain: a n explanation in terms of relational networks - Gil, José María (Revista Chilena de Fonoaudiología, 2014)
Thanks to aphasiology and neuroanatomy, it is known that there are two phonological systems: phonological perception (in Wernicke´s area) and phonological production (in Broca’s area). On the other hand, thanks to Linguistics, we know that the lexicogrammatical system connects meanings with phonology. On this basis, this report aims at showing the way in which relational networks allow us to represent how the two phonological systems, lexico-grammatical and semantics, are connected.